Everybody is somebody - Winkler, Henry, 1945-; Oliver, Lin (Winkler, Henry, 1945- Here's Hank, 2019)
When a well-known author visits their school, Hank and his two best friends get the chance to be her guide for the day and introduce her at an assembly, but the situation forces Hank to find creative ways to hide his struggles with reading.